2019
DOI: 10.21776/ub.civense.2019.00102
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Runoff Coefficient Value on Retention Ponds in Flores Island

Abstract: Flores Island is one of four big islands in NTT province with an area ±13,540 km 2 divided into 8 districts. The area is included in areas with unequal distribution of rainfall. Therefore, the amount of water availability during the dry season is relatively low then require to attempts of rainwater harvesting. One of the alternatives is by building a retention pond. The important parameter in the calculation of water availability is the value of runoff coefficient. The purpose of this research is to invent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Kabupaten Timor Tengah Selatan terletak di Pulau Timor yang memiliki tinggi curah hujan tahunan rata-rata berkisar 1500 mm per tahun (Krisnayanti & Bunganaen, 2018). Musim hujan terjadi pada Bulan Desember -Maret (4 bulan) dengan curah hujan rata-rata bulanan berkisar 300 -500 mm.…”
unclassified
See 1 more Smart Citation
“…Kabupaten Timor Tengah Selatan terletak di Pulau Timor yang memiliki tinggi curah hujan tahunan rata-rata berkisar 1500 mm per tahun (Krisnayanti & Bunganaen, 2018). Musim hujan terjadi pada Bulan Desember -Maret (4 bulan) dengan curah hujan rata-rata bulanan berkisar 300 -500 mm.…”
unclassified
“…Musim hujan terjadi pada Bulan Desember -Maret (4 bulan) dengan curah hujan rata-rata bulanan berkisar 300 -500 mm. Untuk musim kemarau yang terjadi pada Bulan April -November (8 bulan), tinggi curah hujan bulanan berkisar 30 -60 mm (Krisnayanti & Bunganaen, 2018 Data curah hujan menjadi sangat penting dalam proses analisis hidrologi. Sebagian besar fenomena hidrologis yang kompleks terjadi karena variabilitas temporal dan spasial pada data curah hujan.…”
unclassified
“…The longer the recording period, the better the results will be. Many researchers ( Setyawan, Lee & Prawitasari, 2016 ; Putro, 2016 ; Sebayang & Trianing, 2018 ; Chandrasasi, Limantara & Juni, 2020 ; Maulana, Suhartanto & Harisuseno, 2019 ; Krisnayanti et al, 2019 ; Dinar, Agus & Sarino, 2020 ) have used the Mock model to assess water discharges or availability of watersheds. Generally, these studies found the Mock model suitable for evaluating the water balance in specific watersheds.…”
Section: Methodsmentioning
confidence: 99%
“…The highest C value occurs in the month with the highest rainfall (P) reaching 625.0 mm/month as shown in Table 2. The surface runoff coefficient (Cs) value is smaller than the total runoff coefficient (C) which can reach 0.50-0.70, due to the additional base flow [13]. The average value of Cs indicates that around 28% of rainfall that occurred in the study area is transformed into surface runoff.…”
Section: Fig 4 Rainfall-runoff Correlation In Study Areamentioning
confidence: 96%